2014
DOI: 10.1007/s11064-014-1426-8
|View full text |Cite
|
Sign up to set email alerts
|

P2Y13 Receptor-Mediated Rapid Increase in Intracellular Calcium Induced by ADP in Cultured Dorsal Spinal Cord Microglia

Abstract: P2Y receptors have been implicated in the calcium mobilization by the response to neuroexcitatory substances in neurons and astrocytes, but little is known about P2Y receptors in microglia cells. In the present study, the effects of ADP on the intracellular calcium concentration ([Ca(2+)]i) in cultured dorsal spinal cord microglia were detected with confocal laser scanning microscopy using fluo-4/AM as a calcium fluorescence indicator that could monitor real-time alterations of [Ca(2+)]i. Here we show that ADP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 69 publications
5
18
0
Order By: Relevance
“…We found that some previous studies support the notion that P2Y 1 and P2Y 11 receptors are not present in dorsal spinal cord microglia cells. 27 , 38 , 39 Furthermore, Horváth et al discerned that in inflammatory pain rat models, P2Y 12 receptor antagonist did not change the increased level of IL-10 after CFA stimulus. 35 From these observations, we conclude that P2Y 12 and P2Y 13 receptor activation does not lead to increased level of IL-10 in cultured dorsal spinal cord microglia cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that some previous studies support the notion that P2Y 1 and P2Y 11 receptors are not present in dorsal spinal cord microglia cells. 27 , 38 , 39 Furthermore, Horváth et al discerned that in inflammatory pain rat models, P2Y 12 receptor antagonist did not change the increased level of IL-10 after CFA stimulus. 35 From these observations, we conclude that P2Y 12 and P2Y 13 receptor activation does not lead to increased level of IL-10 in cultured dorsal spinal cord microglia cells.…”
Section: Resultsmentioning
confidence: 99%
“…According to some previous studies, 25 27 microglia cells were pretreated with P2Y 12 receptor antagonist MRS2395 (10 μM) and/or P2Y 13 receptor antagonist MRS2211 (10 μM) for 20 min to test the effect of receptor inhibition on ADPβs-induced downstream effects. In some previous studies, Y-27632, SB203580 and PDTC at 5–20 μM were frequently used in order to establish the involvement of ROCK, P38MAPK and NF-κB signaling in cellular responses.…”
Section: Methodsmentioning
confidence: 99%
“…Many responses of purinergic receptors are related to synaptic signal transmission, the interaction between neuron/glia and vascular cells, neurodegenera- tion, inflammatory cells, and neuronal apoptosis. P2Y receptors coupled with a secondary messenger signaling cascade, the GPCRs, which stimulates several intercellular signal pathways, resulting in cell proliferation [23], maturation, and neurotransmission [24]. On the other hand, activation of P2Y receptors could induce Ca 2+ wave and then activate downstream signaling pathways, such as protein kinase C, extracellular signal-regulated kinase, mitogen-activated protein kinases, c-Fos/c-Jun signaling [25], PI3-K/Akt/ Creb pathway, and Jak2/Stat3, Sapk/Jnk signaling [26].…”
Section: Discussionmentioning
confidence: 99%
“…We suggest above that some of the effects of P2Y 13 deletion may reflect an increase of cAMP concentration in the cell, but other signaling pathways may also be associated with the P2Y 13 receptor. These include G q ‐coupled elevations of intracellular [Ca 2+ ] mediated by internal store release and activation of store‐operated calcium channels (Carrasquero et al, ; Zeng et al, ), Erk1/2 activation (Ortega, Perez‐Sen, Delicado, & Teresa Miras‐Portugal, ), and regulation of transcription through a rise in nuclear calcium level and activation of nuclear factor erythroid‐derived 2‐like 2, a transcription factor that regulates the oxidative stress response (Espada et al, ; Lyubchenko et al, ). P2Y 13 may also inhibit Akt (Chatterjee & Sparks, ), which is an important mediator of P2Y 12 ‐mediated actin re‐organization.…”
Section: Discussionmentioning
confidence: 99%
“…P2Y 13 mRNA is upregulated in pathological conditions such as demyelination (Bedard, Tremblay, Chernomoretz, & Vallieres, 2007) and neuropathic pain (Kobayashi, Yamanaka, Yanamoto, Okubo, & Noguchi, 2012;Niu et al, 2017), suggesting a role of this receptor in neuroinflammation. However, its function in microglia, especially under physiological conditions, is still unclear, although it may evoke a rise of [Ca 2+ ] i in response to ADP (Zeng et al, 2014) and be involved in the release of proinflammatory cytokines (Liu et al, 2017). Increasing evidence also supports the notion that ADP may act through P2Y 13 receptors to regulate the structural complexity of microglia (Matyash, Zabiegalov, Wendt, Matyash, & Kettenmann, 2017;Stefani et al, 2018) and contribute to the homeostatic control of adult hippocampal neurogenesis in situ (Stefani et al, 2018).…”
mentioning
confidence: 99%